2022
DOI: 10.1172/jci158708
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TREM2 levels associate with conversion from mild cognitive impairment to Alzheimer’s disease

Abstract: BACKGROUND Soluble triggering receptor expressed on myeloid cells 2 (sTREM2) plays an important role in the clearance of pathological amyloid-β (Aβ) in Alzheimer’s disease (AD). This study aimed to explore sTREM2 as a central and peripheral predictor of the conversion from mild cognitive impairment (MCI) to AD. METHODS sTREM2 and Aβ 1–42 levels in cerebrospinal fluid (CSF) and florbetapir-PET (AV45) images were analyzed for healthy control (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…However, our study is the first to suggest a link between neuronal damage and neurodegeneration with microglial activation in chronic pain states. Additionally, we observed that the difference in sTREM2 CSF levels between chronic pain states in the SNAP group were close to the differences reported between healthy controls and MCI or AD patients 21,30 . Because the CSF levels of sTREM2 and biomarkers of neurodegeneration were analyzed from the same aliquot in ADNI, we were not able to determinate whether microglial activation preceded neuronal damage.…”
Section: Discussionmentioning
confidence: 63%
“…However, our study is the first to suggest a link between neuronal damage and neurodegeneration with microglial activation in chronic pain states. Additionally, we observed that the difference in sTREM2 CSF levels between chronic pain states in the SNAP group were close to the differences reported between healthy controls and MCI or AD patients 21,30 . Because the CSF levels of sTREM2 and biomarkers of neurodegeneration were analyzed from the same aliquot in ADNI, we were not able to determinate whether microglial activation preceded neuronal damage.…”
Section: Discussionmentioning
confidence: 63%
“…TREM2 levels in CSF reveal the reduction before AD and the increase in early AD, and the final decrease again in late AD [69]. Plasma GFAP can more accurately reflect the changes in Aβ burden (not Tau protein) and disease severity in pre-symptomatic AD when compared with GFAP and TREM2 in CSF [70][71][72]. At the same time, TREM2 levels in CSF are closely related to Tau protein [73].…”
Section: Inflammation and Admentioning
confidence: 99%
“…At the same time, TREM2 levels in CSF are closely related to Tau protein [ 73 ]. In addition, a biomarker analysis of healthy elderly, MCI patients, and AD patients has found that MCI patients with low levels of TREM2 in CSF or high levels of plasma TREM2 are more likely to accelerate the progression of AD [ 71 ]. In AD and other neurodegenerative diseases, the function of TREM2-mediated activation of microglia depends on the stage of disease progression and the type of microglia [ 74 ].…”
Section: Inflammation and Admentioning
confidence: 99%
“…Levels of sTREM2 in CSF fall prior to AD clinical onset, rise in early AD, and fall again in late AD. Subjects with higher sTREM2 levels in CSF progress more slowly into and through AD than do subjects with lower sTREM2 levels, suggesting that sTREM2 may protect against AD [ 25 , 26 , 27 , 28 ].…”
Section: The Bbb the Csf And The Neurodegenerative Diseasesmentioning
confidence: 99%